A 22 month prospective assessment of neutralizing and IgG antibody levels against SARS-CoV-2 variants following homologous and heterologous BNT162b2 boosting - Aini Syahida Mat Yassim; Anis Atifah Mohd Hisham; Nik Nur Atiqah Nik Daud; Nur Diana Anuar; Ti-Myen Tan; Rapeah Suppian; Mat Jusoh Siti Asmaa; Amiratul Aifa Mohamad Asri; Maryam Azlan; Nur Suhaila Idris; Rosediani Muhamad; Mohd Nor Norazmi (Scientific Reports)
Abstract This 22-month cohort study investigated the durability and dynamics of humoral immune responses in 327 Malaysians vaccinated with either CoronaVac or BNT162b2 in early 2021, monitored up to 52 weeks following a BNT162b2 booster. Using the ImmuSAFE™ COVID + microarray, we evaluated IgG-S and NAb against Wuhan-Hu and VoCs (Alpha, Beta, Delta, Omicron), as well as IgG-N responses to Wuhan-Hu. BNT162b2 induced higher IgG-S levels and seropositivity than CoronaVac after primary immunization. While a heterologous CoronaVac-BNT162b2 temporarily increased IgG-S levels, long-term IgG-S levels and seropositivity remained comparable between the two groups across all variants. NAb levels were higher in BNT162b2 recipients than in CoronaVac recipients, with homologous BNT162b2 boosters sustaining higher NAb levels for Wuhan-Hu compared to heterologous BNT162b2-CoronaVac. However, responses to other variants varied. Expectedly, CoronaVac uniquely induced IgG-N responses, resulting in elevated IgG-N levels in heterologous BNT162b2-CoronaVac recipients compared to homologous BNT162b2 recipients. Overall, BNT162b2 boosters conferred robust and durable antibody responses regardless of the primary vaccine used. Higher IgG-N levels prior to immunization, compared to pre-pandemic levels, suggest that prior exposure to circulating SARS-CoV-2 VoCs (other than Wuhan-Hu) in Malaysia shaped immune imprinting, influencing responses before immunization with the Wuhan-Hu-based vaccine. Consequently, this study reports higher IgG-S and NAb levels against VoCs—except Omicron—compared to Wuhan-Hu after COVID-19 vaccination.